Development of radiation resistant scintillators based on rare-earth aluminates - Krech, A.V.; Kofanov, D.O.; Khromiuk, I.F.; Okrushko, O.M.; Karavaeva, N.L.; Khabuseva, S.U. (Problems of Atomic Science and Technology, 2022)
LuYAG∶Ce and YAG∶Ce,Ca crystals were obtained by the Czochralski method using tungsten crucibles in reducing surroundings. Crystals (LuₓY₁₋ₓ)₃Al₅O₁₂∶1%Ce and crystals of YAG:Ce,Ca with different concentrations of Ce and Ca were grown. Studies and analyses of their characteristics were carried out. The analysis of their characteristics is based on experimental data that we obtained by measurements of light output, decay time, spectra of luminescence, excitation, and light transmittance. Кристали LuYAG∶Ce та YAG∶Ce,Ca отримані методом Чохральського з використанням вольфрамових тиглів у відновному середовищі. Вирощено кристали (LuₓY₁₋ₓ)₃Al₅O₁₂∶1%Ce та кристали YAG:Ce,Ca з різними концентраціями Ce та Ca. Були проведені дослідження та аналіз їх характеристик. Аналіз їх характеристик ґрунтується на експериментальних даних, які отримані нами шляхом вимірювань світлового виходу, часу згасання, спектрів люмінесценції, збудження та пропускання світла.